Chapter Epilogue Critical reflections and the Way Forward - Noblet, Andrew (Taylor & Francis, 2018)
This conclusion presents some closing thoughts on the key concepts discussed in the preceding chapters of this book. The book highlights that an important guiding principle when developing organizational interventions is to ensure that there's a close fit between the intervention and the context in which the intervention is undertaken. It presents work from some of the world's leading researchers in the field of organizational intervention research. The book also highlights the lack of research attention given to the specific needs of small-medium sized organizations. It argues that the gaps between research, practice, and policy should be closed and that this could happen through evaluating organizational interventions using realist evaluation. The book identifies four factors that were critical to the achievement of positive intervention outcomes. These included participatory decision-making and the co-creation of knowledge, multi-level management support, strong alignment between the intervention and the context, and institutionalizing interventions.